Casca de soja na dieta de equinos submetidos a exercício moderado - Borghi, Roseli Teresinha (2015)
The author of the present work aimed at evaluating the influence of the inclusion of soybean hull (SH) upon the apparent digestibility, the physical-chemical characteristics of feces and the postprandial glycemic responses of horses submitted to moderate-intensity exercise. Five horses were used, aging 11 +2 years old and weighing 483 ± 18 kg. The diets consisted of 60% of Tifton 85 hay (Cynodon spp) and 40% of a pelletized commercial concentrate. The treatments were: substitution of the concentrate for 0%, 10%, 20%, 30% and 40% of SH (Kg/Kg). The experimental period lasted 50 days, being 5 ten-day periods: 7 days for the adaptation to the diet and 3 days of total feces collection. Bromatological analyses of both the foods and of the feces samples were performed for the determination of the apparent digestibility coefficients of the nutrients. The evaluation of the characteristics of the feces comprehended consistency, coloration and pH. For the glycemic tests, 5 mL of blood was collected around 30 minutes before, and 30, 60, 90, 120, 180, 240 and 300 minutes after the administration of the soybean hull homogenized to the concentrate. The experimental delineation used was entirely casualized in Latin square (5x5). For the statistical analyses, the data were submitted to variance analysis. The means were compared with Tukey´s test at 5% of significance. The result demonstrated that there were no effects (P>0.05) of the substitution levels of the concentrate for the soybean hull over the apparent digestibility coefficient of dry matter, organic matter, crude protein, ether extract, nonstructural carbohydrates, hemicellulose, rapidly fermented carbohydrate and energy. However, significant statistical differences were observed (P<0.05) for the apparent digestibility coefficient acid detergent fiber and slowly fermented carbohydrate, with better results for the 30% and 40% substitution levels and a drop in hydrolysable carbohydrate at the 40% level of substitution. Regarding the consistency and coloration, 100% of the horses produced normal (score 3) green-colored feces. There were no statistical differences for the pH value, with means of 6.34. The glucose peak and the area below the glycemic curve were not influenced (P<0.05) by the increasing levels of soybean hull in the diet. It is concluded that the soybean hull can be replaced in 30% and 40%, thus allowing the increase in the apparent digestibility of the fibrous fraction, without causing alterations to the physical-chemical characteristics of both the feces and the glycemic responses of horses undergoing moderate-intensity exercises.